Muscle power and physical dysfunction: A model for tailoring rehabilitation in chronic kidney disease. Issue 10 (6th July 2021) - Wilkinson, Thomas J.; Gore, Eleanor F.; Baker, Luke A.; Watson, Emma L.; Smith, Alice C.
ABSTRACT: Introduction: Chronic kidney disease (CKD) is characterized by adverse physical function. Mechanical muscle power describes the product of muscular force and velocity of contraction. In CKD, the role of mechanical muscle power is poorly understood and often overlooked as a target in rehabilitation. The aims of this study were to investigate the association of mechanical power with the ability to complete activities of daily living and physical performance. Method: Mechanical muscle power was estimated using the sit‐to‐stand‐5 test. Legs lean mass was derived using bioelectrical impedance analysis. Physical performance was assessed using gait speed and 'timed‐up‐and‐go' (TUAG) tests. Self‐reported activities of daily living (ADLs) were assessed via the Duke Activity Status Index. Balance and postural stability (postural sway and velocity) was assessed using a FysioMeter. Sex‐specific tertiles were used to determine low levels of power. Results: One hundred and two non‐dialysis CKD participants were included (age: 62.0 (±14.1) years, n = 49 males (48%), eGFR: 38.0 (±21.5) ml/min/1.73m 2 ). The mean relative power was 3.1 (±1.5) W/kg in females and 3.3 (±1.3) W/kg in males. Low relative power was found in 34% of patients. Relative power was an independent predictor of ADLs (β = .413, p = .004), and TUAG (β = −.719, p < .001) and gait speed (β = .404, p = .003) performance. Skeletal muscle mass was not associated with any outcomes. Conclusion: Knowledge of the factors that mediate physical function impairment is crucial for developing effective interventions. Incorporation of power‐based training focusing primarily on movement velocity may present the best strategy for improving physical function in CKD, above those that focus on increasing muscle mass. SUMMARY AT A GLANCE: This study investigated the association of mechanical power with the ability to complete activities of daily living and physical performance in patients with ND‐CKD. Relative power was found to be an independent predictor of ADL, timed‐up‐and‐go and gait speed; however, skeletal muscle mass was not significantly associated with any outcomes. This study showed important aspects of management of patients with CKD for maintaining and improving of their quality of life.